Completing the first assignment: A case study of the writing processes of a successful and an unsuccessful student. Issue 49 (January 2021) - Wingate, Ursula; Harper, Rowena
Abstract: Previous process-oriented research has predominantly investigated writing processes used by non-native speakers of English (L2) and found that more proficient writers allocate more time to planning and revising than less proficient writers who spend most of their time on formulating. There is so far no exploration of the process use by novice students at university and its relationship to writing performance. Using screen recordings and interviews, we compared the writing processes and behaviours of a successful and unsuccessful student and identified considerable differences in time allocation and the interaction and recursiveness of processes. The findings highlight the importance of integrating a focus on effective process use into academic writing instruction.